Pengaruh Brand Image, Lokasi, dan Store Atmosphere terhadap Niat Beli Ulang pada Pelanggan Indomaret di Wilayah Surabaya - I Wayan Eka Suardyana; Monika Tiarawati (Nomicpedia: Journal of Economics and Business Innovation, 2022)
Although retails for supermarkets and hypermarkets have declined, convenience store type retails have experienced growth and continues to expand throughout Indonesia. Convenience stores are the growing type of retail in Indonesia. The convenience store has not only grown in big cities, but convenience store has begun to succeed in small cities to remote areas close to the residential population. There are a number of minimarket brands in Indonesia, but the two most famous are Indomaret and Alfamart. Even though Indomaret has the most outlets, Alfamart was ranked first in the Top Brand Index (TBI) from 2017 to 2019. This study aims to analyze and discuss the effect of brand image, location, and store atmosphere on repurchase intention for Indomaret’s customers in Surabaya. This study used 220 respondents with non-probability sampling techniques and the method used was snowball sampling. The data collection method is done by distributing questionnaires online. The data analysis technique used in this study is the multiple linear regression analysis techniques. The results found that brand image and store atmosphere had a positive effect on repurchase intention. While location does have not a positive effect on repurchase intention. The results of this study suggest Indomaret and other types of this retail pay attention to the brand image and store atmosphere of their business to increase the repurchase intention of the convenience store